SHARIA BANKING PERFORMANCE INFLUENCED BY MONETARY POLICY - Muhammad Salman; Andri Soemitra; Rifki Ismal (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This article investigates in the literature the influence between Islamic banking performance and monetary policy. With the literature search method using Mendeley Desktop software. The results show that from the various literatures that examine monetary policy and Islamic banking performance, not much has been found that examines and links monetary policy to Islamic banking performance. The search results show that this research still has the potential to be re-examined empirically using both quantitative and qualitative methods, using both primary and secondary data.